Students Activity Recognition By Heart Rate Monitoring In Classroom Using K-means Classification - Hadi Helmi Md Zuraini; Rimuljo Hendradi; Army Justitia; Waidah Ismail (Universitas AirLangga, 2024)
Non-Indexed Publication